The originality of substitution in the theory of Arabic grammar - Al-Zubaidi, Sarah; Al-Fuqara, Saif (Al-Adab Journal, 2025)
The phenomenon of substitution is common in modern linguistic studies in two areas: The first is in distribution (structuralism), and the second is in substitution and its role in textual coherence, there are many studies on this phenomenon in modern linguistics. Studies have examined some aspects of substitution in Arabic grammar. There are topics in the Arabic language about substitution that need further research, to reveal our ancient scholars, awareness of substitutional aspects in linguistic structures.In this research, we attempt to explain the originality of this phenomenon in grammar using many terms and revealing the aspects of the phenomenon in the theory of Arabic grammar, although substitution seems to be a modern linguistic phenomenon? What terms fall under substitution in Arabic grammar? How common is it in ancient linguistic studies?The research seeks to answer the following questions: Is substitution a modern linguistic phenomenon or a traditional phenomenon?The research followed the descriptive approach by tracking the manifestations of substitution and its terms in Arabic grammar. Classifying and analyzing them to arrive at answers to the research questions, it will be for the statistical method Contribution to the study methodology within the limits of the research.